2017
DOI: 10.1111/ina.12428
|View full text |Cite
|
Sign up to set email alerts
|

Local body cooling to improve sleep quality and thermal comfort in a hot environment

Abstract: The effects of local body cooling on thermal comfort and sleep quality in a hot environment were investigated in an experiment with 16 male subjects. Sleep quality was evaluated subjectively, using questionnaires completed in the morning, and objectively, by analysis of electroencephalogram (EEG) signals that were continuously monitored during the sleeping period. Compared with no cooling, the largest improvement in thermal comfort and sleep quality was observed when the back and head (neck) were both coole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 61 publications
4
50
0
1
Order By: Relevance
“…Compared with younger adults, 1,12,13,18 the present study found that the older adults have decreased sleep efficiency, shorter duration of slow wave, and longer wakefulness ( Figure 6, Table 2). Three key changes in sleep of the elderly have been confirmed in previous studies, including reduced deep sleep quantity and quality, reduced sleep efficiency, and sleep fragmentation.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…Compared with younger adults, 1,12,13,18 the present study found that the older adults have decreased sleep efficiency, shorter duration of slow wave, and longer wakefulness ( Figure 6, Table 2). Three key changes in sleep of the elderly have been confirmed in previous studies, including reduced deep sleep quantity and quality, reduced sleep efficiency, and sleep fragmentation.…”
Section: Discussionsupporting
confidence: 44%
“…13 To age well in place, the elderly should be able to control their own thermal environment with their preferred strategies. Local cooling applied to large body sections maintained good sleep and improved thermal comfort of young people in a hot environment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It can be considered as marker of the rate of heat loss from the skin and has been shown to be strongly correlated with thermal sensation votes. 40,44,45 PyroButtons (PyroButton-L, Philadelphia, PA, USA)…”
Section: Physiological Measurementsmentioning
confidence: 99%
“…通过采用床垫和枕头局部冷却, 研究发现, 人体可以 在 32°C 高温环境下维持良好的睡眠质量, 睡眠效率高达 95%, 深睡期达到 158 min [10] . 在此实验中, 床垫中循环流 动的是温度较高的 28°C 的水.…”
Section: 现节能的可行途径unclassified